STUDI KASUS TENTANG PESERTA DIDIK YANG MENGALAMI KECANDUAN GAME ONLINE DI SMP NURUL ISLAM KUBU RAYA - Santosa, Anggi Anggraini; Astuti, Indri; Putri, Amallia (Universitas Tanjungpura, 2024)
This research aims to determine the factors that cause online game addiction, the consequences, and strategies for handling cases among students at Nurul Islam Middle School, Kubu Raya. Using a qualitative approach with descriptive methods, using a case study research design. The case subjects consisted of two people, RA and MU. Data collection techniques are observation, interviews and documentation. The alternative given to the two case subjects was the Rational Emotive Behavior Therapy (REBT) counseling model; cognitive discord techniques, emotion regulation, behavioral techniques and directive counseling. The subject of Case I, the factors are boredom, limited social interaction, enjoyment of playing, financial gain, and enjoyment of playing online games. The impact is decreased achievement, lack of focus in studying, social isolation, health problems, falling asleep in class, neglecting assignments, and being late for school. As a result of treatment, Case Subject I demonstrated improvements in time management for positive activities, desire to break away from gaming addiction, willingness to socialize, increased focus on studies, and improved overall well-being. In Case Subject II, factors include trying games because of the family environment, boredom, seeking attention, and rationalizing excessive gaming as a form of self-esteem. The impact is decreased academic achievement, neglected assignments, health problems, and lack of focus on learning. After being accompanied, Subject II demonstrated the ability to appreciate and utilize time, understand that excessive gaming is detrimental, not neglect tasks, increase focus on learning, and manage the internet wisely